PERSOALAN TANAH ULAYAT MASYARAKAT REMPANG DALAM BAYANG-BAYANG INVESTASI NASIONAL - Yoga Kusuma Yahya; Yusuf Adam Hilman; Syarifah Syarifah (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Baturaja, 2026)
The development of Rempang Eco-City on Rempang Island, Batam, is one of Indonesia's National Strategic Projects that has caused an agrarian conflict involving the government, the Batam Authority (BP Batam), and the indigenous Malay community of Rempang. This community has occupied the area for generations. This article explains the causes of the agrarian conflict in Rempang and describes how national agrarian law regulates the protection of indigenous customary land rights in large-scale development projects. The method used is a literature study with a qualitative descriptive approach, referring to the Basic Agrarian Law Number 5 of 1960 and a number of national scientific journals published between 2021 and 2026. The results show that the customary land rights of the Rempang community remain legally recognized even though they do not hold formal land certificates. This recognition is based on the long duration of their settlement and on Article 18B paragraph (2) of the 1945 Constitution along with Article 3 of the Basic Agrarian Law. The conflict also reflects weak communication between the government and the community during the relocation process. A more appropriate resolution for this case involves dialogue, community participation, and the application of agrarian justice principles.